Carl Schmitt and Simone Weil. Philosophy and Naked Force - Paulina Sosnowska (Phainomena)
The paper is conceptualized on the premise that modern discourses on violence can be read within two fundamental paradigms: the paradigm of force (Simone Weil) and the paradigm of domination (Frankfurt School and its followers). While the first half of the 20th century can be viewed as the exemplification of force, after WWII we are instead faced with violence understood as domination. However, it seems that the 21st century begins with a return of force in a new form. The aim of the paper is to read Carl Schmitt’s political theology as an illustration and extension of Simone Weil’s analysis of force in “The Iliad, or the Poem of Force.” The essay is devoted to an analysis of Schmitt’s fundamental political-legal categories, such as sovereignty, decisionism, and friend–foe opposition as modern translations of force in Weil’s conceptualization: as invasions of brute force into the human order. The paper wishes to be not only an historical-philosophical analysis, but a contribution to the modern project of antifascist education, insofar as the modes of contemporary European authoritarianism (e.g., in Hungary and Poland) more or less overtly refer to the Schmittian legacy. Thus, the contribution aims at an intellectual depotentialization of this legacy and mitigation of the impact of its renaissance.